Circulating macrophage migration inhibitory factor levels and its polymorphisms in systemic lupus erythematosus: A meta-analysis - Bae, S-C.; Lee, Y. H. (Cellular and Molecular Biology, 2017)
The present study aimed to systemically review the evidence regarding the relationship between circulating macrophage migration inhibitory factor (MIF) levels and systemic lupus erythematosus (SLE), as well as the associations between several polymorphisms in the MIF gene and SLE susceptibility. We performed a meta-analysis of serum/plasma levels of MIF in SLE patients and controls and evaluated evidence of associations between the MIF -173 C/G allele and -794CATT5-8 polymorphisms and the associated risk for SLE. Nine studies were included in this meta-analysis. Meta-analysis indicated that MIF levels were significantly higher in the SLE group than in the control group (SMD = 1.154, 95% CI = 0.369–1.938, P = 0.004). Stratification by ethnicity showed significantly higher MIF levels in the SLE group representing Asian populations (SMD = 1.911, 95% CI = 0.871–2.951, P < 0.001). MIF levels were significantly higher in the SLE group than in the control group in the age-and/or sex matched population, but not in the unmatched population (SMD = 1.236, 95% CI = 0.579–1.893, P < 0.001; SMD = 1.118, 95% CI = -0.027–2.263, P = 0.056). However, results of the meta-analysis showed no association between SLE and the MIF -173 C allele, the -794CATT7 allele, and the -794CATT7-MIF-173C haplotype with high heterogeneity. Our meta-analysis demonstrated significantly higher circulating MIF levels in patients with SLE, but no evidence of associations between MIF -173 C/G and -794CATT5-8 polymorphisms and SLE susceptibility.